Implementation of The Understanding by Design (Ubd) Approach To Enchance Student’s Learning in Earth and Solar System Topics At SMPN 1 Rengat - Alisha, Azetta Fikra; Zulhelmi, Zulhelmi; Syafi’i, Muhammad (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aimed to describe students’ learning interest through the implementation of the Understanding by Design (UbD) approach and to determine whether there was a significant difference in learning interest between students taught using UbD and those taught using conventional learning. The study employed a quasi-experimental method with a nonequivalent post-test only control group design involving two classes of 7th grade students at SMPN 1 Rengat. The experimental class was taught using the UbD approach, while the control class received conventional instruction. Descriptive analysis showed that the experimental class achieved a higher average interest score categorized as very high, compared to the control class in the high category. All indicators of learning interest such as enjoyment, attention, participation, and curiosity of student were higher in the UbD class. Inferential analysis using an independent sample t-test confirmed that there was a statistically significant difference in students’ learning interest between the two groups. These results suggest that the UbD approach effectively enhances students’ interest in learning, especially in science topics such as Earth and the Solar System, and can be considered as an alternative teaching strategy to increase student engagement in the classroom.